PENGARUH MANAJEMEN RISIKO, RISIKO KREDIT, DAN RISIKO LIKUIDITAS TERHADAP KEPUTUSAN PEMBERIAN PINJAMAN - Putri, Martha Kartika (Jurnal Akuntansi AKUNESA, 2014)
Development of banking in Indonesia has undergone many changes caused by the development of internal and external factors. The development of the situation followed by the increasing complexity of risk banking activities, thus increasing the application of risk management. Efforts to minimize the risk of loss and an increase in the bank's performance can be done by the bank through the bank's risk management. Some risks are crucial for banks credit risk and liquidity risk, which risk would be beneficial in making lending decisions. Therefore, in this study will be observed the effect of risk management on credit risk and liquidity and lending decisions. The purpose of this study was to analyze the effect of risk management, credit risk and liquidity risk on lending decisions on corporate banking in Indonesia.This researchincludescausal research, using secondary data fromthe 2009-2012financial statementsof banking. The samples are49Banksin 2009, 2011 and 2012, and50Bankin 2010. The results showedsimultaneousmanagementrisk, creditrisk, and liquidity riskaffectlending decisions. Keywords : management risk, credit risk, liquidty risk, lending decision, banking company